ПЭТ-КT төхөөрөмжийн цацрагийн хамгаалалтын тооцоо - Jargalsaikhan, Munkhsaikhan; Zolbadral; S, Odmaa (Scientific transaction of the National University of Mongolia. Physics, 2024)
In this study, the effective dose rate and shielding thickness for a PET/CT facility are calculated by the analytical formula and PHITS code. The calculations at 9 different points in the unshielded and shielded rooms of the PET/CT were performed and the results were compared. The dose administered and the workload were estimated to be 15mCi and 40 patients per week. The required barrier thickness based on the weekly dose limit is 100 µSv for the controlled areas and 20 µSv for uncontrolled areas, corresponding to the 1 mSv/year limit to the general public.